Використання криптовалютних інструментів у забезпеченні розвитку малого бізнесу - Сергієнко, Олена Андріанівна; Застьола, Євген Олексійович; Білоцерківський, Олександр Борисович (ТОВ "ДКС Центр", 2025)
В статті розглянуто можливості створення умов для забезпечення розвитку суб’єктів малого бізнесу в Україні на основі використання криптовалютних інструментів. Доведено, що малий бізнес відіграє надзвичайно важливу роль в соціально-економічній системі, але водночас є дуже чутливим до змін в політичній та економічній ситуації країни. Підвищений рівень чутливості суб’єктів малого бізнесу обумовлює необхідність пошуку нових інструментів, що могли б створити умови для диверсифікації ризиків, притаманних їхній діяльності. Розглянуто перспективи використання криптовалютних інструментів у забезпеченні розвитку малого бізнесу з виокремленням загального, управлінського та прикладного контексту інтеграції криптовалютних операцій в діяльність суб’єктів малого бізнесу. Визначено перспективи подальших досліджень, які доцільно спрямувати на формування механізмів впровадження криптовалютних інструментів та їхньої інтеграції в стратегію розвитку підприємств. The article considers the possibilities of creating conditions for ensuring the development of small business entities in Ukraine based on the use of cryptocurrency instruments. It is proven that small business plays an extremely important role in the socio-economic system. At the same time, this sector of the national economy is very sensitive to changes in the political and economic situation of the country. The increased level of sensitivity of small business entities makes it necessary to search for new instruments that could create conditions for diversifying the risks inherent in their activities. The study was based on the study of scientific publications on the development of small business and the spread of crypto-currency instruments, statistical and analytical materials. The methods of dynamic, comparative, descriptive and contextual analysis were used in the research process. The importance of small business in domestic realities is clarified. The main trends of changes in this area and the features of small business entities in comparison with medium and small enterprises are analyzed. The prospects for using crypto-currency tools in ensuring the development of small businesses are considered, with the general, managerial and applied context of integrating crypto-currency transactions into the activities of small businesses being highlighted. A contextual diagram of integrating crypto-currency transactions into the activities of small businesses is constructed in order to ensure its development. The prerequisites for the emergence and spread of crypto-currency tools are considered. It is established that crypto-currency tools create broad opportunities for entrepreneurs to improve their activities. However, their implementation is associated with significant challenges, only by meeting which enterprises can successfully implement these tools into the practice of domestic business entities. It is determined that the prospects for further research should be directed towards the formation of mechanisms for implementing crypto-currency tools and their integration into the development strategy of enterprises.
Using crypto-currency tools to support small business development
Keywords: малий бізнес; розвиток малого бізнесу; управління; криптовалюта; криптовалютні інструменти; small business; small business development; management; crypto-currency; crypto-currency tools